Co-producing the covid-19 response in Germany, Hong Kong, Lebanon, and Pakistan. (15th February 2021) - Marten, Robert; El-Jardali, Fadi; Hafeez, Assad; Hanefeld, Johanna; Leung, Gabriel M; Ghaffar, Abdul
Abstract : Robert Marten and colleagues highlight the benefits of co-production during covid-19 and call for it to be become embedded in policy making